Senior Leadership Teams and the Agile Organization - Zaccaro, Stephen J.; Hiller, Nathan J.; Klimoski, Richard J. (Taylor & Francis, 2018)
While organizations need to be agile for ongoing success, becoming and remaining agile, nimble, and flexible is difficult, and requires the involvement and alignment of systems, processes, and people. At the epicenter of never-ending push to maintain agility is the senior leadership team. This team is the focus on this book. In this chapter, we describe the purposes for the book, including our intent to build some bridges across different but related scholarly communities around organizational agility. We summarize definitions of agility and present a model that links several key elements and processes that contribution to agile performance. We conclude with a brief summary of each chapter in this volume.